Self‐management interventions for issues identified in a geriatric assessment: A systematic review. Issue 4 (13th December 2021) - Donison, Valentina; Chesney, Tyler R.; Wills, Aria; Santos, Brenda; McLean, Bianca; Alqurini, Naser; Hossain, Nazia; Durbano, Sara; Lemonde, Manon; Alibhai, Shabbir M. H.; Puts, Martine
Abstract: Background: With the development of electronic geriatric assessment (GA), recommendations for self‐management can be provided to patients without the presence of health care providers. Our research question was to identify what self‐management interventions can be used by patients to address issues identified in GA and to determine their effect on patient‐centered outcomes such as quality of life, health, mood, cognition, and functional status. Methods: Searches were conducted on July 13, 2021, by a health sciences librarian in Medline, Embase, CINAHL, PsycInfo, and the Cochrane Library. A combination of database‐specific subject headings and text word searches was used such as self‐management, a key word for each of the geriatric assessment domains and older adults. Two independent reviewers reviewed abstracts and full texts for inclusion and abstracted data. Narrative synthesis was used to summarize findings. Results: Among 28, 520 abstracts reviewed, 34 randomized controlled trials were included. The most frequently studied geriatric domains were mood ( n  = 13 studies), mobility/falls ( n  = 12), quality of life ( n  = 11), and functional status ( n  = 7). The majority of studies demonstrated positive effects on mobility/falls (9 of 12), pain (3 of 5), comorbidity (4 of 4), and medication management (4 of 4). Most studies were of low to moderate quality. All geriatric domains were targeted in at least one study. Conclusions: Low‐ to moderate‐quality studies show a variety of effective self‐efficacy‐targeted interventions exist for older adults to improve several important geriatric domains and related outcomes. However, long‐term effects, validation, and scalability of these interventions remain largely unknown.